2023
DOI: 10.3390/brainsci13020304
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Unplanned Gait Termination According to a Stop-Signal Task Performance: A Preliminary Study

Abstract: There is a correlation between cognitive inhibition and compensatory balance response; however, the correlation between response inhibition and gait termination is not clear. Objectives: The purpose of this study was to investigate the gait parameters of the lower extremity that occurred during unplanned gait termination (UGT) in two groups classified by the stop-signal reaction time (SSRT). Methods: Twenty young adults performed a stop-signal task and an unplanned gait termination separately. UGT required sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The stopping trials were performed similarly to the walking trials, but the subjects were asked to stop upon reaching the force plates [19,20]. That is, their leading limb finished on the second force plate and their trailing limb finished on the ground beside the force plate (PGT condition) or on the first force plate (UGT condition), after which they were required to bring their trailing limbs parallel and maintain an upright standing posture for at least 3 s. In addition, they were asked not to slow down their gait before reaching the force plate [11]. If the participants appeared to have reduced their gait velocity before reaching the force plate, the trial was not analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stopping trials were performed similarly to the walking trials, but the subjects were asked to stop upon reaching the force plates [19,20]. That is, their leading limb finished on the second force plate and their trailing limb finished on the ground beside the force plate (PGT condition) or on the first force plate (UGT condition), after which they were required to bring their trailing limbs parallel and maintain an upright standing posture for at least 3 s. In addition, they were asked not to slow down their gait before reaching the force plate [11]. If the participants appeared to have reduced their gait velocity before reaching the force plate, the trial was not analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported on the mechanisms of PGT and UGT using various analyses, including joint kinematics, and kinetics [9][10][11][12]. However, in these studies comparing the two conditions, only the main braking force that occurred during the stopping phase was analyzed.…”
Section: Introductionmentioning
confidence: 99%